Model Kepemimpinan Nehemia dalam Memobilisasi Jemaat Menghadapi Krisis Gereja Kontemporer - Hendrik Rombe; Jessy Jessy; Sande Roby; Wenniarti Lius; Rilvayanti Rilvayanti (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
Contemporary churches face various crises ranging from declining congregation numbers, internal conflicts, to loss of societal relevance. Many church leaders struggle to mobilize congregations to actively participate in church restoration and growth. This research aims to identify Nehemiah's leadership principles in Nehemiah 2:17-18 relevant for mobilizing congregations facing crises and to formulate a Nehemiah-based leadership model applicable for church leaders. Using qualitative library research methods with exegetical approach and content analysis, this study found six main principles: dependence on God, clear vision, shared problem identification, inspirational communication, congregation empowerment, and perseverance in facing challenges. The formulated leadership model is holistic-integrative, encompassing spiritual, intellectual, social, and managerial dimensions with a fluid leadership approach adaptive to dynamic contexts. This model can help church leaders transform congregations from apathetic to motivated and actively participating in church restoration.